1983
DOI: 10.1111/j.1744-7348.1983.tb02741.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of inoculation methods for determining potato cultivar reaction to black leg

Abstract: SUMMARYTwo methods of inoculating tubers, one by dipping them in an aqueous suspension of Erwinia carotovora subsp. atroseptica, the other by inserting the end of a wooden toothpick charged with undiluted bacteria into the rose‐end near a sprout, were compared over two years for their ability to produce black leg and for their effect on plant growth and yield on a number of cultivars chosen because of expected differences in susceptibility. Although both methods produced a similar rank order for cultivar react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…However, the introgression of the resistance genes into commercial cultivars is difficult because of incompatibility with Solanum tuberosum, complex inheritance, and linkage drag of unwanted traits from the resistant parent (Ahmet et al, 2004;McGrath et al, 2002). Variation for soft rot resistance among S. tuberosum tuberosum cultivars has, however, been shown repeatedly (e.g., Hossain and Logan, 1983;Lapwood and Gans, 1984;Wastie et al, 1988;Rabot et al, 1994). So far, only quantitative variation has been observed (Lyon, 1989), suggesting that resistance to soft rot is primarily of the polygenic, non-specific type.…”
Section: Introductionmentioning
confidence: 90%
“…However, the introgression of the resistance genes into commercial cultivars is difficult because of incompatibility with Solanum tuberosum, complex inheritance, and linkage drag of unwanted traits from the resistant parent (Ahmet et al, 2004;McGrath et al, 2002). Variation for soft rot resistance among S. tuberosum tuberosum cultivars has, however, been shown repeatedly (e.g., Hossain and Logan, 1983;Lapwood and Gans, 1984;Wastie et al, 1988;Rabot et al, 1994). So far, only quantitative variation has been observed (Lyon, 1989), suggesting that resistance to soft rot is primarily of the polygenic, non-specific type.…”
Section: Introductionmentioning
confidence: 90%
“…Methods are only suitable if they are easy to perform, applicable to early vegetative generations and yield reproducible and quantitative data that show good agreement with the resistance of the clones in farmers' fields. Numerous methods for screening of plants in the field [Hossain and Logan, 1983;Lapwood and Legg, 1983;Lapwood and Gans, 1984;Lapwood and Read, 1986a;Gans et al, 1991], or in the glasshouse [Munzert, 1975;Hidalgo and Echandi, 1982;Lapwood and Read, 1986b;Lojkowska and Kelman, 1989] have been described. Field tests correspond most to field conditions but they are expensive to perform and not feasible when only a small amount of seed is available.…”
Section: Introductionmentioning
confidence: 99%
“…The high incidence of blackleg in the waterinoculated controls at NIAB suggests that the inoculation procedure may trigger latent infection even when the pathogen is not being introduced. Hossain & Logan (1983) found that the amount of blackleg in inoculated potato cultivars was quite often disproportionate to yield loss and they suggested that some cultivars showed greater tolerance to the disease than others. In our experiments Pentland Crown showed little black-leg but yield loss was often more severe compared to that of other cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…PtirUulown, Co Armagh BT6.1 s(i|) UK Stem (Lapwood & Read, 1986b). Differences in susceptibility have also been shown in fieldgrown plants, by planting inoculated seed tubers (Hossain & Logan. 1983;Lapwood & Gans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation